Tracing Research Trends of Artificial Intelligence in EFL Context: A Bibliometric Analysis - Gia Salsabila Fratiwi; Muhamad Taufik Hidayat; Lucky Rahayu Nurjamin (Journal of English Language and Education, 2026)
Artificial intelligence (AI) has increasingly transformed English as a Foreign Language (EFL), offering new possibilities for language teaching and learning. This study aims to examine research trends in artificial intelligence within the EFL context through a bibliometric approach. The study focuses on identifying the most productive countries, authors, publishers, and the frequency of publications in this field. Data were collected from the Scopus database and analyzed using a quantitative method with the support of VOSviewer. The findings reveal a significant increase in the number of publications over the past five years, indicating growing research interest in the integration of artificial intelligence in language learning. The study also identified China as the most productive contributing country, while Wang, Y. emerged as a key contributor to the development of this research field. In addition, the European Journal of Education was identified as one of the major platforms for publishing studies related to artificial intelligence in the EFL context. Furthermore, the co-occurrence analysis of keywords shows that current research primarily focuses on writing-related applications, pedagogical integration, and technological development. Frequently occurring keywords such as ChatGPT, writing, and chatbot suggest that AI-assisted tools are widely utilized to support language learning, particularly in improving students’ writing skills. This study provides important implications for researchers, educators, and practitioners by highlighting current research trends and the potential of artificial intelligence to support more effective and personalized language learning. Moreover, this study contributes to the existing literature by providing a comprehensive bibliometric overview of AI research in the EFL context.